Cigarette smoke regulates VEGFR2-mediated survival signaling in rat lungs - Stevenson Christopher S; Arunachalam Gnanapragasam; Edirisinghe Indika; Marwick John A; MacNee William; Kirkham Paul A; Rahman Irfan (BMC, 2010)
Abstract Background Vascular endothelial growth factor (VEGF) and VEGF receptor 2 (VEGFR2)-mediated survival signaling is critical to endothelial cell survival, maintenance of the vasculature and alveolar structure and regeneration of lung tissue. Reduced VEGF and VEGFR2 expression in emphysematous lungs has been linked to increased endothelial cell death and vascular regression. Previously, we have shown that CS down-regulated the VEGFR2 and its downstream signaling in mouse lungs. However, the VEGFR2-mediated survival signaling in response to oxidants/cigarette smoke (CS) is not known. We hypothesized that CS exposure leads to disruption of VEGFR2-mediated endothelial survival signaling in rat lungs. Methods Adult male Sprague-Dawley rats were exposed CS for 3 days, 8 weeks and 6 months to investigate the effect of CS on VEGFR2-mediated survival signaling by measuring the Akt/PI3-kinase/eNOS downstream signaling in rat lungs. Results and Discussion We show that CS disrupts VEGFR2/PI3-kinase association leading to decreased Akt and eNOS phosphorylation. This may further alter the phosphorylation of the pro-apoptotic protein Bad and increase the Bad/Bcl-xl association. However, this was not associated with a significant lung cell death as evidenced by active caspase-3 levels. These data suggest that although CS altered the VEGFR2-mediated survival signaling in the rat lungs, but it was not sufficient to cause lung cell death. Conclusion The rat lungs exposed to CS in acute, sub-chronic and chronic levels may be representative of smokers where survival signaling is altered but was not associated with lung cell death whereas emphysema is known to be associated with lung cell apoptosis.